Derivative impacts on capital markets: a quantitative exploration of capital market stability and management strategies - Zehir, Cemal; Ozyesil, Mustafa; Borodin, Alex; Akturk, Esin Benhur; Huseyinli, Ayten (SPRINGER INDIA, 2026)
This study investigates the effects of derivative products in U.S. markets on key performance criteria of the S&P 500 index and explores management strategies for capital market stability. The performance criteria examined are market volatility, risk, and liquidity of the S&P 500 index. The analysis is based on monthly data from June 2020 to September 2023. The dependent variables are the S&P 500's volatility, risk growth index, and liquidity ratio, with derivative market size and trading activity as the main independent variables. Quantitative results show that derivative usage increases market volatility, enhances market liquidity, and broadens risk distribution across the market. Model diagnostics (inverse roots of AR polynomials and LM tests) confirm the stability and reliability of the Vector Autoregression models. Johansen cointegration tests indicate the existence of long-term equilibrium relationships between derivatives and market indicators. These findings suggest that derivatives exert lasting effects on the S&P 500's performance. Impulse response analysis further reveals the dynamic reactions of the S&P 500 index to shocks in derivative activity. Taken together, the results highlight the dual role of derivatives-providing liquidity and risk-sharing benefits while introducing greater volatility-underscoring the importance of robust management strategies to maintain capital market stability.
Keywords: Derivative; Stability; Volatility; Capital market; Management strategies; RISK; TIME; Engineering